Sprint acceleration characteristics across the Australian football participation pathway - Edwards, T.; Piggott, B.; Banyard, H. G.; Haff, G. G.; Joyce, C. (Sports Biomechanics, 2023)
The aim of this study was to compare the force, velocity and power profiles of a maximal sprint acceleration through different competition levels of the Australian Football (AF) participation pathway. One hundred and sixty-two junior AF athletes across five competition levels including State under 18`s (ST 18), State under 16`s (ST 16), local under 18`s (LOC 18), local under 15`s (LOC 15), and local under 14`s (LOC 14) participated in this cross-sectional study. Velocity-time data from maximal sprint accelerations were analysed to derive athlete`s sprint acceleration characteristics and split times. ST 18 showed a more force-orientated profile than the LOC 18 with moderate differences in relative theoretical maximal force (F0) (7.54%), absolute F0 (10.51%), and slope of the force-velocity relationship (Sf-v) (9.27%). Similarly, small differences were found between ST 18 and ST 16 in relative F0 (4.79%) and Sf-v (6.28%). Moderate to extremely large differences were observed between players competing in older (ST 18, LOC 18, ST 16) compared to younger (LOC 15, LOC 14) competition levels highlighting the potential influence of biological maturation. It is recommended that practitioners working with junior AF players to consider developing a force-orientated sprint acceleration profile to improve sprinting performance.